In RSA: d_K (y)=y^d mod n and n=pq. Define(adsbygoogle = window.adsbygoogle || []).push({});

d_p=d mod(p-1)

d_q=d mod(q-1)

Let

M_p=q^(-1) mod p

M_q=p^(-1) mod q

And

x_p=y^(d_p ) mod p

x_q=y^(d_q ) mod q

x=M_p qx_p+M_q px_q mod n

Show that y^d=x mod n

any help would be appraciated, thanks

**Physics Forums - The Fusion of Science and Community**

# Proof modolu

Have something to add?

- Similar discussions for: Proof modolu

Loading...

**Physics Forums - The Fusion of Science and Community**